Intracranial EEG Seizure-Onset Patterns - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at Montreal Neurological Institute and Hospital, Canada, studied intracranial electroencephalographic seizure-onset patterns associated with different epileptogenic lesions, and defined high-frequency oscillation correlates of each pattern.